Leg muscle recruitment in highly trained cyclists - Chapman, A. R.; Vicenzino, B.; Blanch, P.; Knox, J. J.; Hodges, P. W. (Journal of Sports Sciences, 2006)
In this study, we examined patterns of leg muscle recruitment and co-activation, and the relationship between muscle recruitment and cadence, in highly trained cyclists. Electromyographic (EMG) activity of the tibialis anterior, tibialis posterior, peroneus longus, gastrocnemius lateralis and soleus was recorded using intramuscular electrodes, at individual preferred cadence, 57.5, 77.5 and 92.5 rev · min-1. The influence of electrode type and location on recorded EMG was also investigated using surface and dual intramuscular recordings. Muscle recruitment patterns varied from those previously reported, but there was little variation in muscle recruitment between these highly trained cyclists. The tibialis posterior, peroneus longus and soleus were recruited in a single, short burst of activity during the downstroke. The tibialis anterior and gastrocnemius lateralis were recruited in a biphasic and alternating manner. Contrary to existing hypotheses, our results indicate little co-activation between the tibialis posterior and peroneus longus. Peak EMG amplitude increased linearly with cadence and did not decrease at individual preferred cadence. There was little variation in patterns of muscle recruitment or co-activation with changes in cadence. Intramuscular electrode location had little influence on recorded EMG. There were significant differences between surface and intramuscular recordings from the tibialis anterior and gastrocnemius lateralis, which may explain differences between our findings and those of previous studies.